2021
DOI: 10.32535/ijthap.v4i3.1204
|View full text |Cite
|
Sign up to set email alerts
|

McDonald’s Customer’s Satisfaction Strategies during COVID-19 Pandemic in Malaysia

Abstract: Generally, McDonald’s is recognized as one of the most successful brands worldwide. They are well-known throughout the world for their popular fast food, especially burgers. However, COVID-19 pandemic has impacted various economic sectors, including Food & Beverage. McDonald’s sales have also been impacted when COVID-19’s lockdown restricts the dine-in operation and limits the customer’s satisfaction due to the SOP. Thus, this research aims to identify and analyze the strategies implemented by McDonald’s t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Service delivery is an indicator of organizational effectiveness and performance (Yang et al,2024). When customers demand services in the hospitality industry, it is the responsibility of the service providers to make their requests promptly if not they will not be satisfied, and this will affect the profits of the organization (Edeh et al, 2021b). Customer satisfaction is the perception of a customer concerning the product or service provided by the organization in an effective manner (Hngoi et al, 2023).…”
Section: Organizational Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Service delivery is an indicator of organizational effectiveness and performance (Yang et al,2024). When customers demand services in the hospitality industry, it is the responsibility of the service providers to make their requests promptly if not they will not be satisfied, and this will affect the profits of the organization (Edeh et al, 2021b). Customer satisfaction is the perception of a customer concerning the product or service provided by the organization in an effective manner (Hngoi et al, 2023).…”
Section: Organizational Effectivenessmentioning
confidence: 99%
“…Conversely, surveys have shown that work attitude is sometimes linked to negative work behavior from the employees who demonstrate it (Edeh et al, 2021b;Heimerl et al, 2020). To discourage this menace in the work setting, Ogilo et al (2020) advocate for adequate sensitization of employees regarding the goals and culture of the organization they are working with.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
“…Customer satisfaction is one of an organization's most common and important aspects, especially in the fast-food industry (Edeh et al, 2021). According to Hansemark and Albinson (2004), satisfaction is an overall customer attitude towards a service provider, or an emotional reaction to the difference between what customers anticipate and what they receive, regarding the fulfillment of some needs, goals, or desires.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…According to Chambers (2020), Customer loyalty is the act of continually choosing one company's products and services over competitors. Customer loyalty is at the forefront of the industry and has positive or negative value based on customer support level (Edeh et al, 2021). A loyal customer isn't easily influenced by price or availability.…”
Section: Introductionmentioning
confidence: 99%
“…McDonald's, as a global fast-food giant, has attracted significant attention from researchers due to its ability to adapt to changing consumer tastes and preferences. McDonald's brand is different from its competitors not only in terms of customer loyalty, but also in terms of quality, consistency, and standardization they had always maintain (Edeh et al, 2021). This research paper aims to analyze the factors that affect customer preference for McDonald's, providing valuable insights for the fast-food industry.…”
Section: Introductionmentioning
confidence: 99%